Phytochemical analysis and antibacterial activity of Khaya senegalensis bark extracts on Bacillus subtilis, Escherichia coli and Proteus mirabilis - Abdullahi Aliyu; Alkali BR; Yahaya MS; Garba A; Adeleye SA; Gashua MM; Sa‘Adatu I; Gugong V; Daneji AI (International Journal of Phytomedicine, 2016)
The aqueous and ethanol extracts of the bark of Khaya senegalensis were screened for their phytochemical constituents and preliminary antibacterial activity against Bacillus subtilis, Escherichia coli and Proteus mirabilis. The minimum inhibitory concentration (MIC) of the plant on the tested organisms was determined using multiple tubes method. Alkaloids, anthraquinones, glycosides, tannins and steroids were detected in both extracts. The ethanol and aqueous extracts of the plant showed antibacterial activity against B. subtilis and E. coli, with the aqueous extracts having more activity than those of ethanol. However the growth of P. mirabilis was not inhibited by either of the extracts. The MIC value was determined to be 50 mg/ml for B. subtilis and E. coli. The results are suggestive of considerable antibacterial activity of K. senegalensis and may justify its use in the treatment of bacterial diseases by herbalists or traditional healers.